Regenerative Endodontic Management of an Immature Molar Using Calcium Hydroxide and Triple Antibiotic Paste: a Two-Year Follow-Up - Mohannad Alasqah; Sulthan Ibrahim Raja Khan; Khalid Alfouzan; Ahmed Jamleh (Hindawi Limited, 2020)
The regenerative endodontic procedure (REP) is considered a viable treatment option for immature teeth with necrotic pulp and periapical radiolucency which can facilitate continued root formation. In this report, an immature necrotic mandibular molar received REP in three appointments wherein chemomechanical debridement was performed with a sequential application of nonsetting calcium hydroxide (in the whole canal) and triple antibiotics paste (in the root's middle third) dressings in the first and second appointments, respectively. In the third appointment, blood clots were created in the root canals. MTA was placed over the blood clots and the tooth was restored with a composite filling and stainless-steel crown. Recall appointments were performed for two years where the tooth was deemed asymptomatic clinically and a complete root formation with significant periapical healing was evident radiographically. More cases are required to warrant the feasibility of this disinfection protocol.